ASXL1 and SETBP1 mutations promote leukaemogenesis by repressing TGFβ pathway genes through histone deacetylation. Issue 1 (December 2018) - Saika, Makoto; Inoue, Daichi; Nagase, Reina; Sato, Naru; Tsuchiya, Akiho; Yabushita, Tomohiro; Kitamura, Toshio; Goyama, Susumu
Abstract Mutations inASXL1 andSETBP1 genes have been frequently detected and often coexist in myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML). We previously showed that coexpression of mutant ASXL1 and SETBP1 in hematopoietic progenitor cells induced downregulation of TGFβ pathway genes and promoted the development of MDS/AML in a mouse model of bone marrow transplantation. However, whether the repression of TGFβ pathway in fact contributes to leukaemogenesis remains unclear. Moreover, mechanisms for the repression of TGFβ pathway genes in ASXL1/SETBP1-mutated MDS/AML cells have not been fully understood. In this study, we showed that expression of a constitutively active TGFβ type I receptor (ALK5-TD) inhibited leukaemic proliferation of MDS/AML cells expressing mutant ASXL1/SETBP1. We also found aberrantly reduced acetylation of several lysine residues on histone H3 and H4 around the promoter regions of multiple TGFβ pathway genes. The histone deacetylase (HDAC) inhibitor vorinostat reversed histone acetylation at these promoter regions, and induced transcriptional derepression of the TGFβ pathway genes. Furthermore, vorinostat showed robust growth-inhibitory effect in cells expressing mutant ASXL1, whereas it showed only a marginal effect in normal bone marrow cells. These data indicate that HDAC inhibitors will be promising therapeutic drugs for MDS and AML withASXL1 andSETBP1 mutations.